Implementation of Pai Extracurricular Lessons in Developing Students' Soft Skills at Tunas Harapan Private Vocational School, Batang Serang, Langkat Regency - M. Ikhzan Rafit Manurung; Sokon Saragih; Khairuddin (Sean Institute, 2026)
The purpose of this study is to determine the PAI extracurricular program in developing students' soft skills at Tunas Harapan Batang Serangan Private Vocational School, the activeness of students in PAI extracurricular activities at the school, and what factors hinder the effectiveness of PAI extracurricular implementation in developing students' soft skills at Tunas Harapan Batang Serangan Private Vocational School. This study uses a qualitative method with a qualitative descriptive approach and empirical methods. Data collection techniques used in this study are interviews, observations and documentation studies. Data validity techniques used are credibility, transferability, dependability, confirmability. After the data was analyzed, the results of the study showed that the activities of the Tunas Harapan Private Vocational School Extracurricular Program, Langkat Regency, were in the form of reading the Qur'an and interpreting it in the activity, kultum, PHBI commemoration and annual Ramadan events such as breaking the fast together and tadarus in congregation and providing takjil. This Extracurricular Program has quite good activity because each class is required to send its delegates to participate in this extracurricular so that its activity is maintained well and continues to cycle. The most obvious obstacle experienced by teachers implementing extracurricular programs to develop soft skills is the inherently demanding nature of vocational school students, and the reluctance of many to engage in the program. Consequently, these obstacles sometimes disrupt participation and reduce activeness.